Habitus Petani Sawah Berlahan di Bawah 0.5 Hektar dalam Memenuhi Nafkah Keluarga - Purwito Rahmadi; Bambang Santosa (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
The purpose of this research is to know the habitus of rice paddy farming under 0.5 hectares in fulfilling the family's living. This research uses qualitative methods with a case study approach. The data-sensing technique uses purposive sampling. The results of the research conducted can be known that habitat farmers Habitus with less than 0.5 hectares of land in the village of Columnayan in the effort to fulfill household, not only rely on farming activities. By carrying out other alternatives to farming activities are expected to solve the problems of living in household fulfillment.